Loss of Foreign DNA Inserts from Barley Stripe Mosaic Virus Vectors—Potential Consequences for Use in Functional Genomics Studies - Steven R. Scofield (International Journal of Plant Biology, 2023)
Barley stripe mosaic virus (BSMV)-based vectors are frequently used in virus-induced gene silencing (VIGS) and, more recently, viral overexpression (VOX) studies in wheat. Two general strategies are employed to initiate infection in wheat plants with BSMV in VIGS and VOX studies. One method involves the direct infection of wheat using viral RNA produced via the in vitro transcription of BSMV constructs. The second class utilizes viral replication in an intermediate host plant to produce large amounts of BSMV viral particles that are then used to inoculate wheat plants. This study was designed to examine the potential for BSMV-VIGS constructs to rearrange during replication in the intermediate host and result in initiating the VIGS studies with a virus that is significantly different from the original experimental construct. It is shown that in the case of BSMV-VIGS constructs harboring a PDS-silencing fragment, significant rearrangement can occur during replication in the intermediate host that has the potential to introduce artifactual experimental outcomes.